Rancang Bangun Aplikasi Sistem Parkir Mobil Menggunakan Sensor Infra Red di Rumah Sakit Aminah Blitar - Bambang Tri Wahjo Utomo (Jurnal Ilmiah Teknologi Informasi Asia, 2012)
Along with the development of today's technology has a lot of parking spaces that use a computerized system. Particularly in Aminah hospital parking system that is used is still quite manual. Manager with the park interpreter using the number of parking tickets being used. Thus, the manager does not have valid data in the distribution percentages are used because the data using only data on the number parking ticket. Therefore, the design created a motor vehicle car counter. So with this tool can monitor the number of motor vehicles, especially four-wheel vehicle in the parking lot entrance of the incoming data will be used as a comparison between the number of parking tickets that are used by the number of vehicles entering. Thus, managers can calculate the percentage for the interpreter to the hospital parking lot. This device consists of an infrared sensor that consists of a transmitter and receiver so that if the car is blocked by vehicles associated with the application via a computer program to calculate the number of vehicles entering the parking area. Keywords: Parking, Sensor, infrared, Aplication